Comparison of relapse rates and of mucosal abnormalities after healing of duodenal ulceration and after one year's maintenance with cimetidine or sucralfate: a light and electron microscopy study. Issue 5 (May 1989) - Tovey, F I; Husband, E M; Yiu, Y C; Baker, L; McPhail, G; Lewin, M R; Jayaraj, A P; Clark, C G
Abstract : Forty six patients with endoscopically diagnosed duodenal ulceration were randomly allocated to treatment with either sucralfate 1 g qds (n = 24) or cimetidine 200 mg tds and 400 mg nocte (n = 22). When the ulcers healed, a maintenance dose of sucralfate 1 g bd or cimetidine 400 mg nocte was given for one year (or until relapse if earlier). Biopsies of duodenal mucosa adjacent to ulcer sites for light and electron microscopy were obtained before and after healing and again after one year's maintenance if the ulcer remained healed. Duodenal biopsies were also taken from 20 age and sex matched controls. Rates of healing and relapse during maintenance did not differ between the two treatments, although relapses occurred earlier with cimetidine. In the three year post-maintenance follow up period 10/13 cimetidine patients relapsed compared with four of 11 sucralfate patients (p less than 0.05), the relapses occurring significantly earlier in the cimetidine treated patients (p less than 0.05). Mucosal biopsies from both treatment groups still showed considerable abnormalities after healing. During maintenance, however, the sucralfate scores fell significantly (p less than 0.02) to near control levels unlike the cimetidine scores which remained raised at pretreatment values. The histological and ultrastructural changes were not predictive of later relapse. These findings favour the use of sucralfate in preference to cimetidine for maintenance treatment in the prevention of relapse of healed duodenal ulcers.